Institution-Building as State-Building in Weak States : Iraq as a Case Study - Zubir R. Ahmed; Handren Ahmad Eahya (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study aims to discuss and analyses the theoretical understanding of institution-building as state-building. It examines Fukuyama’s conceptual understanding of institutions and applies it in the context of state-building in Iraq. The significance of the subject is that it is one of the most controversial topics in contemporary politics and international relations. A political analysis method was used and the research data dealt with by examining a number of variables. It will argue that the process of state-building in Iraq since 2003 has been complex and challenging, marked by a series of successes, setbacks, and ongoing struggles. Furthermore, Iraq’s post-Saddam era has been marked by efforts to build and strengthen various state institutions. These institutions include the judiciary, security forces, and other government bodies responsible for essential functions such as education, healthcare, infrastructure, and finance. However, the process of institution-building in Iraq has faced significant challenges, which include ethno-sectarian divisions, insurgencies, and external influences that have complicated the political landscape and hindered efforts to create stable institutions. Corruption and inefficiency have also been persistent issues that have hindered the development of a strong governing framework. This study concludes that Iraqi political institutions are deeply fragmented.